2019
DOI: 10.3889/oamjms.2019.030
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Fasting and Post 75 G Glucose Loading of Glucagon-Like Peptide 1 Levels in Obese and Non-Obese Subjects

Abstract: BACKGROUND: Prevalence of obesity increased sharply recently; it was associated with an increased prevalence of several cardiometabolic diseases. Reduced glucagon-like peptide 1 (GLP-1) secretion is observed among obese subjects in many studies, and it may mediate the failure of insulin secretion response to food intake. AIM: To evaluate the pattern of fasting and post 75 g glucose loading of GLP-1 levels in obese and non-obese subjects. METHODS: An experimental study on the pattern of GLP-1 levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…9 Nugraha et al research in 2018 showed that the patterns of GLP-1 levels post glucose loading were similar in obese and non-obese subjects, and there was a tendency of lower GLP-1 levels in fasting state and post-glucose loading in obese subjects compared to non-obese subjects. 10 In this study, in addition to assessing the response of giving 75 gram oral glucose loading to an increase in 30 th minute GLP1 levels in a population of diabetic subjects, it also investigated the relationship between glomerular filtration rate and GLP1 levels both fasting and post-loading of glucose. Basically, the secreted GLP1 hormone is immediately eliminated from circulation in less than five minutes, therefore the half-life of GLP1 in circulation is only about one to two minutes.…”
Section: Discussionmentioning
confidence: 99%
“…9 Nugraha et al research in 2018 showed that the patterns of GLP-1 levels post glucose loading were similar in obese and non-obese subjects, and there was a tendency of lower GLP-1 levels in fasting state and post-glucose loading in obese subjects compared to non-obese subjects. 10 In this study, in addition to assessing the response of giving 75 gram oral glucose loading to an increase in 30 th minute GLP1 levels in a population of diabetic subjects, it also investigated the relationship between glomerular filtration rate and GLP1 levels both fasting and post-loading of glucose. Basically, the secreted GLP1 hormone is immediately eliminated from circulation in less than five minutes, therefore the half-life of GLP1 in circulation is only about one to two minutes.…”
Section: Discussionmentioning
confidence: 99%